Effects of rice husk biochar on selected soil properties and nitrate leaching in loamy sand and clay soil - Mohammad Ghorbani; Hossein Asadi; Sepideh Abrishamkesh (International Soil and Water Conservation Research, 2019)
Biochar is a product of pyrolysis of biomass in the absence of oxygen and has a high potential to sequester carbon into more stable soil organic carbon (OC). Despite the large number of studies on biochar and soil properties, few studies have investigated the effects of biochar in contrasting soils. The current research was conducted to evaluate the effects of different biochar levels (0 (as control), 1% and 3%) on several soil physiochemical properties and nitrate leaching in two soil types (loamy sand and clay) under greenhouse conditions and wet-dry cycles. The experiment was performed using a randomized design with three levels of biochar produced from rice husks at 500 °C in three replications. Cation exchange capacity increased significantly, by 20% and 30% in 1% and 3% biochar-amended loamy sand soil, respectively, and increases were 9% and 19% in 1% and 3% biochar-amended clay soil, respectively. Loamy sand soil did not show improvement in aggregate indices, including mean weight diameter, geometric mean diameter, water stable aggregates and fractal dimension, which was contrary to the results for the clay soil. Rice husk biochar application at the both rates decreased nitrate leaching in the clay soil more than in the loamy sand. Our study highlights the importance of soil type in determining the value of biochar as a soil amendment to improve soil properties, particularly soil aggregation and reduced nitrate leaching. The benefits of the biochar in the clay soil were greater than in the loamy sand soil. Keywords: Soil incubation study, Carbon sequestration, Biochar rates, Soil texture, Water stable aggregate